The Transformative Influence of La Varenne's Le Cuisinier Francois (1651) on French Culinary Practice - Fine, Leon G. (Frontiers in Nutrition, 2020)
Is it impossible to conceive of there being a publication which could have had an overriding influence on culinary practice or eating preferences, even at a local level.? When there was a historical absence of cookbooks for a half century, as there was in France in the first half of the 17th century, it is argued herein that the advent of a single cookbook in 1651, Le Cuisinier Francois, authored by La Varenne, could have had a transformational influence on culinary practice over the ensuing half century. The book went into more than 50 subsequent editions in the second half of the century. La Varenne stated clearly that his intent was to provide a guide for professional cooks, however, it is hypothesized in this article that the widespread and enduring success of the book was due to its attraction to and acquisition by the general public, including household cooks. This can be ascribed to the facts that (i) there had been no French cookbook describing novel culinary approaches in the preceding 50 years, (ii) La Varenne’s concise, uncomplicated and practical style of presentation of recipes and (iii) his selection of principal ingredients, which were within the reach of the household cook and which reflected the availability of foods at the time of writing. Furthermore, because Le Cuisinier Francois was laid out according to widely observed religious practices, finding the best options for the appropriate day of the month became an easy task for the user. La Varenne initiated a departure from an earlier style of heavily spiced cooking, to one which was based upon natural flavors, a limited use of spices and uncomplicated cooking methods. Thus, rather than assuming that the enduring popularity of the book was due to its widespread use by culinary professionals, it is argued that its style and substance must have imparted a sense of empowerment and confidence in the home cook and that, in these terms, La Varenne’s influence on culinary practice was far more widespread and was truly transformative, accounting for the remarkable success of the Le Cuisinier Francois.